Practical Application of Quality Tools in the Cast Iron Foundry - Ulewicz, Robert (Manufacturing Technology Journal, 2014)
New requirements placed to products, and hence to materials from which they are produced resulted in widespread use of instruments of quality assurance. Depending on destination of the product, its manufacturing process is burdened with the need to implement quality assurance systems, recording and analysing data, and also a process of continuous improvement. The article presents the results of practical use of selected quality tools in iron foundry. In order to determine the level of incompatibility of manufactured products the analysis was carried out based on the use of Ishikawa diagram and Pareto-Lorenz method. The results of the above analysis were defined as a starting point to develop a dendrogram and to determine the variant solution to the problem using programming of decision-making process, there was also developed diagram of the manufacturing process of iron castings.
Keywords: Quality Tools; Cast Iron Foundry